Lactic acid production from waste sugarcane bagasse derived cellulose - Adsul, Mukund G.; Varma, Anjanikumar; Gokhale, Digambar V. (Green Chemistry, 2007)
Production of L(+) lactic acid from sugarcane bagasse cellulose, one of the abundant biomass materials available in India, was studied. The bagasse was chemically treated to obtain a purified bagasse cellulose sample, which is much more amenable to cellulase enzyme attack than bagasse itself. This sample, at high concentration (10%), was hydrolyzed by cellulase enzyme preparations (10 FPU g(-1) cellulose) derived from mutants generated in our own laboratory. We obtained maximum hydrolysis (72%), yielding glucose and cellobiose as the main end products. Lactic acid was produced from this bagasse cellulose sample by simultaneous saccharification and fermentation (SSF) in a media containing a cellulase enzyme preparation derived from Penicillium janthinellum mutant EU1 and cellobiose utilizing Lactobacillus delbrueckii mutant Uc-3. A maximum lactic acid concentration of 67 g l(-1) was produced from a concentration of 80 g l(-1) of bagasse cellulose, the highest productivity and yield being 0.93 g l(-1) h(-1) and 0.83 g g(-1), respectively. The mutant Uc-3 was found to utilize high concentrations of cellobiose (50 g l(-1)) and convert it into lactic acid in a homo-fermentative way. Considering that bagasse is a waste material available in abundance, we propose to valorize this biomass to produce cellulose and then sugars, which can be fermented to products such as ethanol and lactic acid.

Lipase of aspergillus niger NCIM 1207: a potential biocatalyst for synthesis of isoamyl acetate - Mhetras, Nutan; Patil, Sonal; Gokhale, Digambar V. (Indian Journal of Microbiology, 2010)
Commercial lipase preparations and mycelium bound lipase from Aspergillus niger NCIM 1207 were used for esterification of acetic acid with isoamyl alcohol to obtain isoamyl acetate. The esterification reaction was carried out at 30 degrees C in n-hexane with shaking at 120 rpm. Initial reaction rates, conversion efficiency and isoamyl acetate concentration obtained using Novozyme 435 were the highest. Mycelium bound lipase of A. niger NCIM 1207 produced maximal isoamyl acetate formation at an alcohol/acid ratio of 1.6. Acetic acid at higher concentrations than required for the critical alcohol/acid ratio lower than 1.3 and higher than 1.6 resulted in decreased yields of isoamyl acetate probably owing to lowering of micro-aqueous environmental pH around the enzyme leading to inhibition of enzyme activity. Mycelium bound A. niger lipase produced 80 g/l of isoamyl acetate within 96 h even though extremely less amount of enzyme activity was used for esterification. The presence of sodium sulphate during esterification reaction at higher substrate concentration resulted in increased conversion efficiency when we used mycelium bound enzyme preparations of A. niger NCIM 1207. This could be due to removal of excess water released during esterification reaction by sodium sulphate. High ester concentration (286.5 g/l) and conversion (73.5%) were obtained within 24 h using Novozyme 435 under these conditions.
Keywords: Aspergillus niger NCIM 1207; Fusel oil; Isoamyl acetate formation; Mycelium bound lipase; Novozyme 435

Lignocellulose processing: a current challenge - Singhvi, Mamata S.; Chaudhari, Shivani; Gokhale, Digambar V. (RSC Advances, 2014)
Lignocellulosic biomass, of which inedible crops are a renewable source, is expected to become one of the key renewable energy resources in the near future, to deal with global warming and the depletion of conventional fossil fuel resources. It also holds the key to supplying society's basic needs for the sustainable production of chemicals and fuels without impacting the human food supply. Despite this, the production of 2nd generation biofuels and chemicals has not yet been commercialized. Therefore, the challenges involved in the production of lignocellulosic biomass derived fuels and chemicals must be addressed. The search for economic pretreatment methods has been recognized as one of the main hurdles for the processing of biomass to biofuels and chemicals. The conversion of all biomass components, lignin in particular, would greatly contribute to the economic viability of biomass based processes for 2nd generation biofuels and chemicals. The highly organized crystalline structure of cellulose presents an obstacle to its hydrolysis. Hydrolysis of lignocellulose carbohydrates into fermentable sugars requires a number of different biomass degrading enzymes such as cellulases and hemicellulases. Still, a number of technical and scientific issues within pretreatment and hydrolysis remain to be solved. Depending on the raw material and pretreatment technology, the enzyme mixtures must be designed to degrade biomass carbohydrates. Rapid advances in enzyme, microbial and plant engineering would provide the necessary breakthroughs for the successful commercialization of biomass derived fuels and chemicals.

Lignocellulosic biomass: hurdles and challenges in its valorization - Singhvi, Mamata S.; Gokhale, Digambar V. (Applied Microbiology and Biotechnology, 2019)
Lignocellulosic biomass (LCB) is globally available and sustainable feedstock containing sugar-rich platform that can be converted to biofuels and specialty products through appropriate processing. This review focuses on the efforts required for the development of sustainable and economically viable lignocellulosic biorefinery to produce carbon neutral biofuels along with the specialty chemicals. Sustainable biomass processing is a global challenge that requires the fulfillment of fundamental demands concerning economic efficiency, environmental compatibility, and social responsibility. The key technical challenges in continuous biomass supply and the biological routes for its saccharification with high yields of sugar sources have not been addressed in research programs dealing with biomass processing. Though many R&D endeavors have directed towards biomass valorization over several decades, the integrated production of biofuels and chemicals still needs optimization from both technical and economical perspectives. None of the current pretreatment methods has advantages over others since their outcomes depend on the type of feedstock, downstream process configuration, and many other factors. Consolidated bio-processing (CBP) involves the use of single or consortium of microbes to deconstruct biomass without pretreatment. The use of new genetic engineering tools for natively cellulolytic microbes would make the CBP process low cost and ecologically friendly. Issues arising with chemical characteristics and rigidity of the biomass structure can be a setback for its viability for biofuel conversion. Integration of functional genomics and system biology with synthetic biology and metabolic engineering undoubtedly led to generation of efficient microbial systems, albeit with limited commercial potential. These efficient microbial systems with new metabolic routes can be exploited for production of commodity chemicals from all the three components of biomass. This paper provides an overview of the challenges that are faced by the processes converting LCB to commodity chemicals with special reference to biofuels.
Keywords: Biomass pretreatment; Biomass supply chain; Cellulosic ethanol; Consolidated bio-processing; Lignocellulosic biomass (LCB)